IMF Staff papers : Volume 26 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1979)
In this paper, a general equilibrium model of a small open economy is constructed that reproduces the pattern of price, wage, and exchange rate behavior stressed by the 'vicious circle' view in the case where the primary source of disturbances in the economy is monetary. The paper also undertakes a dynamic analysis of the issue of policy effectiveness and relates the effectiveness of monetary and fiscal policy to the speed of price and wage adjustment, the degree of monetary accommodation, and the openness of the economy. Finally, a policy that allows a country to escape from an inflationary spiral without undergoing a prolonged period of unemployment is proposed. The validity of this policy proposal relies heavily on the assumption that capital markets are highly integrated. With integrated capital markets, a policy of fiscal stimulus is shown to lead to an appreciation of the exchange rate, a reduction in the rate of inflation of wages and prices, and a temporary increase in output and employment. This policy, combined with an appropriate degree of monetary constraint, is shown to be capable, in theory, of breaking a wage-price-exchange rate spiral.